Sex differences in the association between skeletal muscle energetics and perceived physical fatigability: the Study of Muscle, Mobility and Aging (SOMMA) - Emma L. Gay; Paul M. Coen; Stephanie Harrison; Reagan E. Garcia; Yujia Qiao; Bret H. Goodpaster; Daniel E. Forman; Frederico G. S. Toledo; Giovanna Distefano; Philip A. Kramer; Sofhia V. Ramos; Anthony J. A. Molina; et al. (GeroScience, 2024)

Lower muscle mitochondrial energetics is associated with greater phenotypic frailty in older women and men: the Study of Muscle, Mobility and Aging - Theresa Mau; Haley N. Barnes; Terri L. Blackwell; Philip A. Kramer; Scott R. Bauer; David J. Marcinek; Sofhia V. Ramos; Daniel E. Forman; Frederico G. S. Toledo; Russell T. Hepple; Stephen B. Kritchevsky; Steven R. Cummings; et al. (GeroScience, 2023)

Active thrust tectonics along the western slope of the Central Andes southernmost Pampean flat-slab segment (∼33°S, Chile): The Cariño Botado fault system - J. Estay; L. Pinto; G. Easton; G.P. De Pascale; M. Troncoso; S. Carretier; S.L. Forman (Geomorphology, 2023)

Diets of deepwater oreos (Oreosomatidae) and orange roughy Hoplostethus atlanticus - J. S. Forman; P. L. Horn; D. W. Stevens (Journal of Fish Biology, 2016)
The diets of black oreo Allocyttus niger , smooth oreo Pseudocyttus maculatus , spiky oreo Neocyttus rhomboidalis and orange roughy Hoplostethus atlanticus were determined from examination of contents of 240, 311, 76 and 415 non‐empty stomachs, from fishes sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand. Hoplostethus atlanticus had an opportunistic predatory strategy with a broad diet dominated by prawns and mesopelagic teleosts, but with substantial components of mysids and cephalopods. Pseudocyttus maculatus was strongly specialized on gelatinous zooplankton (jellyfish and salps). Allocyttus niger consumed mainly salps and hyperiid amphipods, and to a lesser extent fishes, prawns, mysids and copepods. Neocyttus rhomboidalis primarily consumed salps, along with mysids, euphausiids and fishes. Only P. maculatus did not exhibit significant ontogenetic variation in diet. The diets were also influenced by year and bottom depth. Differences in the distributions and diets of the four species probably reduce conflicts in resource use.

Last interglacial vegetation and climate history from the Portuguese coast - T. A. MINCKLEY; J. A. HAWS; M. M. BENEDETTI; S. C. BREWER; S. L. FORMAN (Journal of Quaternary Science, 2015)
We examine the Atlantic maritime vegetation history from Praia Rei Cortiço, Portugal, to understand natural vegetation patterns and infer climatic conditions during the transition from the last interglacial to early glacial periods. Optically stimulated luminescence dating of quartz grains from sediments surrounding the 1.3‐m‐thick organic deposit date the section to within 120–89 ka. Pollen data were used to reconstruct the vegetation history and determine a range of possible past climates using an ensemble of seven modern analogue approaches. A five‐part environmental sequence transitioned from heath‐pine‐dominated communities, deciduous hardwood forests and pine forests to heathlands surrounded by steppe‐like environments. Mixed temperate and Mediterranean forest elements existed during the last interglacial period at Praia Rei Cortiço, suggesting a proximal limit to these floras. Abundant Fagus pollen (>6%) suggests local beech populations existed within maritime forests of the Iberian Atlantic margin, representing a greater distribution of this genus during interglacial periods than has previously been recognized. Climate reconstructions indicate that variations in moisture availability may have been a major driver of the observed environmental changes.

Moon phase influences the diet of southern Ray's bream Brama australis - P. L. Horn; J. S. Forman; M. R. Dunn (Journal of Fish Biology, 2013)
Diet composition of the southern Ray's bream Brama australis was examined from stomach contents of 399 specimens sampled by bottom trawl on Chatham Rise to the east of South Island, New Zealand, over 3 years. Prey items were predominantly mesopelagic fishes and crustaceans. Multivariate analysis indicated that moon phase explained more of the diet variability than any other predictor examined. It appears likely that diet composition is influenced by a combination of changes in both tidal flows and illumination. Different combinations of prey were consumed by B. australis at different times of the lunar cycle. An influence of moon phase on feeding by fishes has rarely been reported, but it is likely that moon phase influences the diets of other species that specialize in mesopelagic prey. The most important prey group by mass for B. australis was Myctophidae (primarily Lampanyctodes hectoris ), followed by Stomiiformes (primarily Maurolicus australis ) and shrimps ( Sergestes spp). An ontogenetic shift in diet was observed, from numerical dominance by small crustaceans including amphipods and euphausiids (with some fishes) in smaller (mass B. australis to pelagic teleost prey (with a few larger crustaceans) in larger (>1440 g) B. australis .

Diet and trophic niche of Antarctic silverfish Pleuragramma antarcticum in the Ross Sea, Antarctica - M. H. Pinkerton; J. Forman; S. J. Bury; J. Brown; P. Horn; R. L. O'Driscoll (Journal of Fish Biology, 2013)
The diet of Antarctic silverfish Pleuragramma antarcticum was evaluated by examining stomach contents of specimens collected in the Ross Sea (71°–77° S; 165°–180° E) in January to March 2008. Pleuragramma antarcticum (50–236 mm standard length, L S ) and prey items were analysed for stable‐isotopic composition of carbon and nitrogen. According to index of relative importance ( I RI ), which incorporates frequency of occurrence, mass and number of prey items, the most important prey items were copepods (81% I RI over all specimens), predominantly Metridia gerlachei and Paraeuchaeta sp., with krill and fishes having low I RI (2·2 and 5·6% I RI overall). According to mass of prey ( M ) in stomachs, however, fishes ( P. antarcticum and myctophids) and krill dominated overall diet (48 and 22% M , respectively), with copepods being a relatively minor constituent of overall diet by mass (9·9% M ). Piscivory by P. antarcticum occurred mainly in the extreme south‐west of the region and near the continental slope. Krill identified to species level in P. antarcticum stomachs were predominantly Euphausia superba (14·1% M ) with some Euphausia crystallophorias (4·8% M ). Both DistLM modelling (PRIMER‐permanova+) on stomach contents (by I RI ) and stepwise generalized linear modelling on stable isotopes showed that L S and location were significant predictors of P. antarcticum diet. Postlarval P. antarcticum (50–89 mm L S ) consumed exclusively copepods. Juvenile P. antarcticum (90–151 mm L S ) consumed predominantly krill and copepods by mass (46 and 30% M , respectively). Small adult P. antarcticum (152–178 mm L S ) consumed krill, fishes and copepods (37, 36 and 15% M , respectively). Large adult P. antarcticum (179–236 mm L S ) consumed predominantly fishes and krill (55 and 17% M , respectively), especially in the north (near the Ross Sea slope) and in the SW Ross Sea. Amphipods were occasionally important prey items for P. antarcticum (western Ross Sea, 39% M ). General concordance between stomach contents and trophic level of P. antarcticum and prey based on δ 15 N was demonstrated. Pleuragramma antarcticum trophic level was estimated as 3·7 (postlarval fish) and 4·1 (fish aged 3+ years).

Dietary partitioning by two sympatric fish species, red cod ( Pseudophycis bachus ) and sea perch ( Helicolenus percoides ), on Chatham Rise, New Zealand - Peter L. Horn; Jeff S. Forman; Matthew R. Dunn (Marine Biology Research, 2012)

The cag PAI is intact and functional but HP0521 varies significantly in Helicobacter pylori isolates from Malaysia and Singapore - H.-M. A. Schmidt; S. Andres; C. Nilsson; Z. Kovach; N. O. Kaakoush; L. Engstrand; K.-L. Goh; K. M. Fock; D. Forman; H. Mitchell (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

A novel technique for isolating functional mast cells from the heart - L. G. Morgan; S. P. Levick; T. G. Voloshenyuk; D. B. Murray; M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2008)

Rat cardiac mast cell maturation and differentiation following acute ventricular volume overload - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2006)

Spontaneous histamine secretion during isolation of rat cardiac mast cells - M. F. Forman; G. L. Brower; J. S. Janicki (Inflammation Research, 2004)